Pleural Fluid Cholesterol in Differentiating Exudative and Transudative Pleural Effusion - A. B. Hamal; K. N. Yogi; N. Bam; S. K. Das; R. Karn (Pulmonary Medicine)
Objectives. To study the diagnostic value of pleural fluid cholesterol in differentiating transudative and exudative pleural effusion. To compare pleural fluid cholesterol level for exudates with Light’s criteria. Design. Cross sectional descriptive study. Settings. Medical wards of Tribhuvan University Teaching Hospital. Methods. Sixty two cases of pleural effusion with definite clinical diagnosis admitted in TUTH were taken and classified as transudates (19) and exudates (43). The parameters pleural fluid protein/serum protein ratio (pfP/sP), pleural fluid LDH/ serum LDH ratio, pleural fluid LDH (pfLDH) and pleural fluid cholesterol (pCHOL) were compared with clinical diagnosis with regard to their usefulness for distinguishing between pleural exudates and transudates. Results. The pCHOL values determined were for exudates, for transudates, the differences between the transudates and others are statistically significant (). It is seen that pfP/sP ratio has a sensitivity of 81.4% and specificity of 82.6%; pfLDH/sLDH ratio has a sensitivity of 86% and specificity of 94.7% and pCHOL with sensitivity of 97.7% and specificity of 100% for differentiating exudative and transudative PE. Conclusion. The determination of pCHOL is of great value for distinguishing between pleural exudates and transudates and should be included in routine laboratory analysis of pleural effusion.